The Effect of Human Resource Competence, Organizational Commitment, and Systems Quality on Individual Use of Accrual Based Accounting System Application At Statistics Indonesia (BPS) - Nanik Dwi Saratih; Willy Abdillah (AFEBI Accounting Review, 2017)
Minister Regulation No. 71/2015, all government institutions must use an accrual-based system in the financial report in 2015. Therefore, Indonesian government institutions need some adequate human resource competence, high organizational commitment and qualified information systems regarding reliable, accurate, comprehensive and relevant to decision-making of financial statement. This study examines the effect of human resource competencies, organizational commitment and quality of the system to the accrual based accounting system application usability at Statistics Indonesia (BPS). The population of this study were 513 government agencies at BPS. Using paper-based survey, data was gathered from 129 respondent based accrual institutional accounting system application services. The data analysis technique was the multiple linear regression analysis. Results showed that human resource competence and organizational commitment has a positive effect on individual use of the accrual-based accounting system application. The implication for stakeholders and further research are discussed.Keywords: Human Resource Competence, Information Systems, Organizational Commitment, Systems Quality